Use of biofeedback (BFB) in the treatment of fecal incontinence after surgical correction of anorectal malformations by posterior sagital anorectoplasty (PSARP) - Martins, José Luiz; Pinus, José (São Paulo Medical Journal, 1997)
OBJECTIVE: To evaluate biofeedback(BFB)responses to rehabilitation techniques and physical exercises in incontinent or partially continent anorectal malformations patients after posterior sagital anorectoplasty (PSARP). DESIGN: Prospective study. SETTING: Pediatric Surgery - Department of Surgery - UNIFESP-EPM. PATIENTS:The authors report on 14 patients with anorectal malformations (4 with partial fecal incontinence after primary PSARP; 6 with fecal incontinence after primary PSARP; 3 with partial fecal incontinence after secondary PSARP; and 1 with fecal incontinence after secondary PSARP). All patients were rehabilitated via a BFB program of exercises in order to improve the function of the anal sphincteric muscular complex for a period of 1 -3 years. MAIN OUTCOME MEASURE: Clinical and manometric control. RESULTS: After BFB, of 4 partially continent patients after primary PSARP, 3 became continent; of 6 incontinent patients after primary PSARP, 4 became continent; of 3 partially continent patients after secondary PSARP, 1 became continent,1 showed no improvement and 1 became incontinent (infection + abscess + fibrosis + important anorectal stenosis). The incontinent patient after secondary PSARP showed no improvement. CONCLUSION: The authors concluded that BFB, used at the appropriate time with patient collaboration, is an important complement to the anatomical reconstruction of anorectal malformations in order to achieve good development and contractile functioning of the sphincteric muscular complex.